Comparison of Biological Properties and Clinical Application of Mesenchymal Stem Cells from the Mesoderm and Ectoderm - Zhenning Wang; Meng Huang; Yu Zhang; Xiaoxia Jiang; Lulu Xu (Stem Cells International)
Since the discovery of mesenchymal stem cells (MSCs) in the 1970s, they have been widely used in the treatment of a variety of diseases because of their wide sources, strong differentiation potential, rapid expansion in vitro, low immunogenicity, and so on. At present, most of the related research is on mesoderm-derived MSCs (M-MSCs) such as bone marrow MSCs and adipose-derived MSCs. As a type of MSC, ectoderm-derived MSCs (E-MSCs) have a stronger potential for self-renewal, multidirectional differentiation, and immunomodulation and have more advantages than M-MSCs in some specific conditions. This paper analyzes the relevant research development of E-MSCs compared with that of M-MSCs; summarizes the extraction, discrimination and culture, biological characteristics, and clinical application of E-MSCs; and discusses the application prospects of E-MSCs. This summary provides a theoretical basis for the better application of MSCs from both ectoderm and mesoderm in the future.